2003
DOI: 10.1136/ijgc-00009577-200311000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of c-erbB-2/HER2 expression in advanced uterine cervical carcinoma with para-aortic lymph node metastasis treated with radiation therapy

Abstract: This paper looks at whether c-erbB-2/HER2 expression in uterine cervical carcinoma before treatment is a predictive parameter of prognosis in patients with para-aortic lymph node metastasis (PALN) in advanced disease after treatment with radiation therapy (RT). Twenty-one patients with PALN at the first visit and/or during follow-up and treated with RT for PALN lesions were studied. Their clinical stages were IIIB or greater and they were referred to the National Institute of Radiological Sciences Hospital for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
11
1
1
Order By: Relevance
“…We found that expression of the HER2 ⁄ neu oncoprotein and HER2 ⁄ neu gene amplification are uncommon events in cervical neoplasia. This contrasts with a number of previous publications in the literature, including reports of a correlation between HER2 ⁄ neu overexpression and poor response to radiotherapy and worse overall survival (11,24,25).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that expression of the HER2 ⁄ neu oncoprotein and HER2 ⁄ neu gene amplification are uncommon events in cervical neoplasia. This contrasts with a number of previous publications in the literature, including reports of a correlation between HER2 ⁄ neu overexpression and poor response to radiotherapy and worse overall survival (11,24,25).…”
Section: Discussioncontrasting
confidence: 99%
“…24 In patients with cervical carcinoma, a relation has been shown between HER-2 expression and local resistance to radiotherapy as well as between HER-2 expression and prognosis. [25][26][27] In a study by Akamatsu et al, 28 HER-2 expression in patients with esophageal carcinoma was associated with local resistance to chemo-radiotherapy but not linked with prognosis. Furthermore, the authors reported that tumors with HER-2 expression were resistant to cisplatinumbased chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from local invasion, lymphatic cell spread from the primary cervical lesion sequentially leads to pelvic, paraaortic and supraclavicular lymph node metastases. The incidence of paraaortic lymph node metastases increases with tumour stage (IB 6%; IIB 19%; IIIB 29%; V 30%) (Nibe et al 2003;Ahmed et al 2004). The Gynecologic Oncology Group identified paraaortic lymph node metastases and tumour size as the two most significant prognostic factors regarding survival (Singh et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lymph node metastases have major impact on the risk of local and distant cancer recurrence as well as disease-specific survival (Munkarah 2002). Five-year survival rates in patients with paraaortic lymph node metastases treated with standard-fraction irradiation range between 15% and 50% (Kupets et al 2002;Nibe et al 2003;Ahmed et al 2004). The overall frequency of left supraclavicular lymph node metastases is less than 5%.…”
Section: Introductionmentioning
confidence: 99%